Shallower Root Spatial Distribution Induced by Phosphorus Deficiency Contributes to Topsoil Foraging and Low Phosphorus Adaption in Sugarcane (Saccharum officinarum L.) - Yi, Ke; Li, Xiaofeng; Chen, Diwen; Yang, Shu; Liu, Ying; Tang, Xinlian; Ling, Guizhi; Zhao, Zunkang (Frontiers in Plant Science, 2022)
Low phosphorus (P) availability in acid soils is one of the main limiting factors in sugarcane (Saccharum officinarum L.) production. Reconstruction of the root system architecture (RSA) is a vital mechanism for crop low P adaption, while the RSA of sugarcane has been little-studied because of its complex root system. In this study, reconstruction of the RSA and its relationship with P acquisition were investigated in a P-efficient sugarcane genotype ROC22 (R22) and two P-inefficient genotypes Yunzhe 03-103 (YZ) and Japan 2 (JP). An efficient dynamic observation room was developed to monitor the spatiotemporal alternation of sugarcane root length density (RLD) and root distribution in soil with heterogeneous P locations. The sugarcane RSA was reconstructed under P deficiency, R22 had an earlier response than YZ and JP and presented an obvious feature of root shallowness. Compared with the normal P condition, the shallow RLD was increased by 112% in R22 under P deficiency while decreased by 26% in YZ, and not modified in JP. Meanwhile, R22 exhibited a shallower root distribution than YZ and JP under P deficiency, supported by 51% and 24% greater shallow RLD, 96% and 67% greater shallow root weight, respectively. The ratio of shallow RLD to total RLD in R22 was 91% greater than YZ, and the ratio of shallow root weight to total root weight in R22 was greater than that of YZ and JP by 94% and 30%, respectively. As a result, R22 had a higher shoot P accumulation than YZ and JP, which thereby increased the relative leaf sheath inorganic P concentration by 47% and 56%, relative shoot biomass by 36% and 33%, and relative cane weight by 31% and 36%, compared with YZ and JP under P deficiency, respectively. We verified the reliability and efficiency of a dynamic observation room and demonstrated that a shallower root distribution contributed to improving topsoil foraging, P acquisition, and low P adaption under P deficiency in sugarcane. Therefore, a shallower root distribution merits consideration as an evaluation trait for breeding P efficient sugarcane genotypes and genetic improvement.